Utilization of gambier leaf extract (Uncaria gambier roxb) as antibacterial and natural dyes in making liquid bath soap with natrium lauryl ether sulfate. Issue 1 (January 2022) - Nurhayati, C; Susilawati, N; Susanto, T; Marthalia, W; Nugroho, A K
Abstract: Research has been carried out on the liquid soap formulation of Gambier leaf extract ( Uncaria gambier Roxb) from the by-product of the Gambier Industry with natrium lauryl ether sulfate as raw material. Gambier extract contains catechins and catechu tannic acids which have antibacterial, pharmacological, and other toxic properties. In addition, it contains tannins for natural dyes. The purpose of this research is to develop a liquid bath soap formulation with Gambier extract, which has high antibacterial properties using stable, safe, and comfortable natural dyes according to the Indonesian National Standard (SNI). This research went through several stages using 6 (six) variations of gambier extract waste as follows: 0, 2, 4, 6, 8, and 10%. The quality testing of liquid soap used chemical and physical properties tests, including pH, viscosity, foam stability, total plate number, specific gravity, free alkaline, texture, color, and aroma, then compared to SNI 4085-2017 about the quality requirements for liquid bath soap. The results showed that the usage of by-products of the gambier production process, not only used as natural dyes, would also strengthen bacterial inhibition which was indicated by a decrease in the value of the Total Bacterial Plate Number. The more the gambier waste concentration, the more the red color and antiseptic indicated by decreasing of the total plate number. The best treatment in this study was A4 treatment (addition of 6% gambier waste) with pH value 8.8, viscosity 170.98 cP foam stability (t0 =95.6mm, t5 =77.1mm), total bacterial plate number 1.05 x 10 2 colonies/g, specific gravity 1.0404 mg/L, free alkaline <0.008%, preferable hedonic (texture, color, and aroma).